2020
DOI: 10.21203/rs.3.rs-37899/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthy Lifestyle Behaviors Are Major Predictors of Mental Wellbeing During COVID-19 Pandemic Confinement: A Study on Adult Arabs in Higher Educational Institutions

Abstract: Background In previous times, infectious diseases affected the quality of human life during home confinement. This study investigated the influence of home confinement during the COVID-19 pandemic outbreak on lifestyle, mental wellbeing, nutritional status, and sleeping pattern. Method: An online multicategory questionnaire was distributed to collect Demographical information and combined the following tools: Food Frequency Questionnaire (FFQ), International Physical Activity Questionnaire (IPAQ), WHO-5 well… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We report high rate of deteriorated mental wellbeing in our study including sense of saddness, loss of interest in doing loved things and experience of anxiety. In previous work in a study done in UAE, lower mental quality was associated was more prevalent among females and better mental wellbeing was associated with better diet, better physical activity and better sleep scores (11). Corona virus pandemic was de nitely linked to less ability to go out and perform outdoor activities which could be associated with reduced hormones which could in uence the mood such as endorphins and serotonin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We report high rate of deteriorated mental wellbeing in our study including sense of saddness, loss of interest in doing loved things and experience of anxiety. In previous work in a study done in UAE, lower mental quality was associated was more prevalent among females and better mental wellbeing was associated with better diet, better physical activity and better sleep scores (11). Corona virus pandemic was de nitely linked to less ability to go out and perform outdoor activities which could be associated with reduced hormones which could in uence the mood such as endorphins and serotonin.…”
Section: Discussionmentioning
confidence: 96%
“…Corona virus pandemic was de nitely linked to less ability to go out and perform outdoor activities which could be associated with reduced hormones which could in uence the mood such as endorphins and serotonin. In addition this could be linked to exposure to UV radiation and so lower formation of vitamin D which is protective from depression (11). A longitudinal study among a sample of participants from UK indicated across waves of pandemic showed that symptoms of anxiety, entrapment decreased with time, but depressive symptoms did not change and positive feelings increased which could be a positive indication on the direction of mental wellbeing (12).…”
Section: Discussionmentioning
confidence: 99%